2006
DOI: 10.1186/1471-2334-6-20
|View full text |Cite
|
Sign up to set email alerts
|

Automated extraction protocol for quantification of SARS-Coronavirus RNA in serum: an evaluation study

Abstract: Background: We have previously developed a test for the diagnosis and prognostic assessment of the severe acute respiratory syndrome (SARS) based on the detection of the SARS-coronavirus RNA in serum by real-time quantitative reverse transcriptase polymerase chain reaction (RT-PCR). In this study, we evaluated the feasibility of automating the serum RNA extraction procedure in order to increase the throughput of the assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Earlier reports found that magnetic particle-based automated systems could be inferior [10] , close [11] , [12] or superior [4] to manual column methods for recovering viral RNA from various sample types, moreover, the automated systems generally brought about high precision and hands-on time reduction. Our data demonstrated that Maxwell 16-S RNA extraction had good linearity and precision over a wide concentration range and higher sensitivity in detection of stock flu-v in VTM than the QIAamp method.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports found that magnetic particle-based automated systems could be inferior [10] , close [11] , [12] or superior [4] to manual column methods for recovering viral RNA from various sample types, moreover, the automated systems generally brought about high precision and hands-on time reduction. Our data demonstrated that Maxwell 16-S RNA extraction had good linearity and precision over a wide concentration range and higher sensitivity in detection of stock flu-v in VTM than the QIAamp method.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, SARS corona (SARS-CoV) appears as a Flu-like illness that advances to respiratory failure, pneumonia and, in certain instances, death [36] , [37] , [38] , [39] , [40] . SARS-related mortality rate is relatively higher than influenza or other common infections of the respiratory tract [40] , [41] , [42] , [43] , [44] .…”
Section: Sars-covmentioning
confidence: 99%
“…There are many benefits to this approach, including speed, accuracy, and a reduction in the exposure of laboratory personnel to the virus. On the market, there are many RNA extraction apparatuses that could be implemented in SARS-CoV-2 diagnostics, with some examples such as the QIAcube Connect (Qiagen, Hilden, Germany), EZ1 Advanced XL (Qiagen) [ 30 ], NucliSENS easyMAG (bioMerieux, Marcy-l’Étoile, France) [ 10 ], EMAG (bioMerieux) [ 31 ], and also those adapted to higher biosafety levels in instruments such as the MagNA Pure LC (Roche Diagnostics, Basel, Switzerland) [ 32 ].…”
Section: Molecular Biology Techniques Targeting Sars-cov-2 Nucleic Acidsmentioning
confidence: 99%